Islamophobia in contemporary Britain: the evidence of opinion polls, 1988-2006 - Field, Clive D. 19XX- (Islam and Christian-Muslim relations, 2007)
British attitudes towards Islam and Muslims are examined on the basis of 104 public opinion polls conducted between 1988 and 2006, 90 of them since 2001. Many of these surveys were undertaken at national crisis points of one sort or another for which Islam and Muslims could not avoid being seen as causal factors. Nine high-level conclusions are drawn from this evidence. There has been increasing Islamophobia, not least since 2001. A stereotypical picture of British Muslims in the eyes of the majority population has emerged, Muslims being seen as slow to integrate into mainstream society, feeling only a qualified sense of patriotism, and prone to espouse anti-Western values that lead many to condone so-called Islamic terrorism. To an extent, these stereotypes reflect the reality of Muslim views, as displayed in 29 polls conducted among the British Muslim community, mainly since 2001.